Fiction Anthropologism (Literatures of the World: Poetics, Mentality and Spirituality, 2014)
The article considers the position of Ukrainian literary criticismabout anthro-pologism in literature. Anthropological aspects of the work «Podrostok» by Fyodor Dostoevsky were analyzed. The author considers the dominant images, and features of psychology, as one of the pillars of anthropologism.
Keywords: anthropologism; spirituality; contradiction; dominant image